2016
DOI: 10.1002/hep.28887
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of PGK1 promotes liver cancer cell proliferation and tumorigenesis

Abstract: These findings demonstrate a novel regulation of PGK1 as well as its important role in liver cancer progression. (Hepatology 2017;65:515-528).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
171
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(190 citation statements)
references
References 45 publications
7
171
0
3
Order By: Relevance
“…PGK1, an important enzyme in metabolic glycolysis, has been considered as an oncogene in various human malignancies . PGK1 is upregulated in HCC and negatively correlated to poor survival in patients with HCC . Consistently, we also observed significant overexpression of PGK1 mRNA and protein in HCC specimens.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…PGK1, an important enzyme in metabolic glycolysis, has been considered as an oncogene in various human malignancies . PGK1 is upregulated in HCC and negatively correlated to poor survival in patients with HCC . Consistently, we also observed significant overexpression of PGK1 mRNA and protein in HCC specimens.…”
Section: Discussionsupporting
confidence: 86%
“…These results indicated that PGK1 is a direct target of miR‐450b‐3p in HCC. Notably, the inhibitory effect of miR‐450b‐3p on HCC proliferation could be abrogated by overexpression of PGK1 which has been reported to promote the tumorigenesis and development of HCC …”
Section: Discussionmentioning
confidence: 99%
“…In our surgical samples we have identified three distinct isoforms of PGK1 all increased with respect to the normal tissues. Many types of cancers, including those of the breast [47], the colon [48], the liver [49] and others, have been shown to exhibit an increased expression of PGK1. Indeed, it has been demonstrated that, in addition to its role as a glycolytic enzyme, PGK1 may act as a promoter of cancer progression and induce chemoresistance for some type of drugs [47,48].…”
Section: Phosphoglycerate Kinase 1 Pgk1 (Pgk1)mentioning
confidence: 99%
“…Cancer cells exhibit a series of common features, including uncontrolled proliferation, resistance to programmed cell death, and enhanced metastasis ability [1,2]. Of these, alteration of metabolic pathways is regarded as a driving force of tumor initiation and progression [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…PGK1 and pyruvate kinase M2 (PKM2) are the only enzymes that control production of ATP during aerobic glycolysis in cancer cells [1,3]. In addition to the important role of PGK1 in glycolysis, there are reports of its role in cancer.…”
Section: Introductionmentioning
confidence: 99%